2018
DOI: 10.3390/educsci8030104
|View full text |Cite
|
Sign up to set email alerts
|

Development of Digital Competence in Secondary Education Teachers’ Training

Abstract: Digital competence is one of the eight key competences for life-long learning developed by the European Commission, and is a requisite for personal fulfilment and development, active citizenship, social inclusion, and employment in a knowledge society. To accompany young learners in the development of competence, and to guarantee optimal implementation of information and communication technologies (ICTs), it is necessary that teachers are, in turn, literate. We had 43 secondary school teachers in initial train… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 14 publications
(26 reference statements)
7
75
0
18
Order By: Relevance
“…Considering digital competence as one of the key competences recognized by the European Commission in the educational field, research continues to show, however, low ratings in this competence (mainly in content creation and problem solving) by future teachers [40]. These results are consistent with those obtained in the study by Cabero and Barroso [22], in which the competences associated with the TPACK model were evaluated in a sample of 1368 university students, and whose results revealed training lacks in the dimensions of pedagogical knowledge and of content.…”
Section: Discussionmentioning
confidence: 99%
“…Considering digital competence as one of the key competences recognized by the European Commission in the educational field, research continues to show, however, low ratings in this competence (mainly in content creation and problem solving) by future teachers [40]. These results are consistent with those obtained in the study by Cabero and Barroso [22], in which the competences associated with the TPACK model were evaluated in a sample of 1368 university students, and whose results revealed training lacks in the dimensions of pedagogical knowledge and of content.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of ICT skills, identified in the digital competence framework, include information literacy, communication using digital technologies, and the ability to resolve problems situated in digital environments [43]. Napal et al [44] indicated the importance of developing teachers' ICT competencies with particular emphasis on information literacy and safety, as well as ability to create digital contents. Professional development activities provide opportunities for teachers to engage in observation, discussion, planning, and practicing new skills.…”
Section: Skills and Practices On The Use Of Ictmentioning
confidence: 99%
“…Personal characteristics, such as gender and age, can influence how teachers adopt different types of teaching innovation [19,20].…”
mentioning
confidence: 99%